Perceived Employee Productivity in the Banking Industry: The Effect of Knowledge Transfer, Transformational Leadership Style, and Workplace Collaboration - Lotho, Glenn; Bagasbas, Dianne Michaela; Marcos, Michael Lito; Nicolas, Hanna Gennis; Vinluan, Judiel Raphael (International Journal of Business and Social Science Research, 2026)
This study examined how Knowledge Transfer, Transformational Leadership Style, and Workplace Collaboration influence Perceived Employee Productivity among bank employees in Metro Manila. Data were gathered from 291 employees working in universal banks across the region using a survey-based questionnaire to assess these factors. Structural Equation Modeling (SEM) via WarpPLS was employed to analyze the data. The findings indicated that Knowledge Transfer, Transformational Leadership Style, and Workplace Collaboration all had positive and significant impacts on Perceived Employee Productivity. Of the three, Workplace Collaboration exerted the most substantial influence, followed by Knowledge Transfer and then Transformational Leadership Style. The results underscore that fostering a collaborative environment-bolstered by effective knowledge sharing and transformational leadership-can enhance employees’ perceived productivity and drive overall organizational performance. Consequently, the study recommends that organizations prioritize strengthening collaboration and knowledge-sharing practices and actively promote transformational leadership to boost productivity among banking sector employees.